Effect of tomato extract supplementation against high-fat diet-induced hepatic lesions - Melendez-Martinez, Antonio J.; Nascimento, Andre F.; Wang, Yan; Liu, Chun; Mao, Yilei; Wang, Xiang-Dong (HepatoBiliary Surgery and Nutrition, 2013)
Higher intake of tomatoes or tomato-based products has been associated with lower risk for liver cancer. In this study, we investigated the effects of supplementing tomato extract (TE), which contains mainly lycopene (LY) and less amounts of its precursors, phytoene (PT) and phytofluene (PTF) against highfat- diet related hepatic inflammation and lipid profiles, and carcinogenesis. Four groups of rats were injected with a hepatic carcinogen, diethylnitrosamine (DEN) and then fed either Lieber-DeCarli control diet (35% fat, CD) or high fat diet (71% fat, HFD) with or without TE supplementation for 6 weeks. Results showed that the supplementation of TE significantly decreased the multiplicity of both inflammatory foci and altered hepatic foci (AHF) expressing placental form glutathione-S transferase (p-GST) in the liver of HFD-fed rats. High-performance liquid chromatography (HPLC) analysis showed that TE supplementation results in a significantly higher accumulation of both PT and PTF than LY in livers of rats. In addition, the TE supplementation led to a decrease of plasma cholesterol levels but an overall increase in hepatic lipids which is associated with changes in the genes on lipid metabolism, including the peroxisome proliferator-activated receptor gamma (PPARγ) and the sterol-regulatory element binding protein (SREBP-1). These data suggest that TE supplementation decreases hepatic inflammation and plasma total cholesterol associated with high dietary fat intake. Moreover, TE supplementation results in an accumulation of hepatic PT and PTF as well as increased lipogenesis suggesting further investigation into their biological function(s).